Unraveling microbial community diversity and succession of Chinese Sichuan sausages during spontaneous fermentation by high-throughput sequencing - Wang, Xinhui (J Food Sci Technol, 2019)
The microbial community diversity and succession of Chinese Sichuan sausages during the spontaneous fermentation were demonstrated using high-throughput sequencing technology. The bacterial diversity was abundant and the succession of bacterial community along the direction of Lactobacillus spp. increased and Weissella spp. decreased. While fungal diversity was single and trace fungal population was detected. The core functional microbiota were lactic acid bacteria, including Lactobacillus spp., Weissella spp. and Pediococcus spp. In initial fermentation, Weissella spp. was the dominant bacteria and its relative abundance was 49.84%, but then its relative abundance decreased to 11.96% during fermentation before recovering to 26.74% at the end of fermentation. Meanwhile, Lactobacillus spp. rose from 24.70 to 55.74% and became the dominant genus. Moreover, Pediococcus spp. increased from 0.06 to 18.05% on day 20 but then decreased to 1.89% on day 30. These results revealed that the primary microorganisms contributing to spontaneous fermentation of Chinese Sichuan sausages were bacteria, while eukaryotic microorganisms such as yeast scarcely contributed to fermentation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-019-03781-y) contains supplementary material, which is available to authorized users.